Educating for the sustainable development goals through service-learning: University students’ perspectives about the competences developed - Ribeiro, Luísa Mota; Miranda, Francisca; Themudo, Carmo; Gonçalves, Helena; Bringle, Robert G.; Rosário, Pedro; Aramburuzabala, Pilar (Frontiers in Education, 2023)
The purpose of this study was to examine the perceived impact of a Service-Learning (SL) experience titled “Educating for Sustainable Development Goals (SDGs),” at the Porto campus of Universidade Católica Portuguesa (UCP), in which 15 university students from different programs were challenged to train other students about the SDGs. The main aim of the SL project was to raise awareness about the SDGs among the recipients (200 high school students, 20 students from a University in Angola and 40 from a University in Brazil). Besides the development of soft skills in UCP students, the learning objectives also focused on training socially responsible citizens who can take the SDGs into their future professions and help create a better and more sustainable world. UCP students were asked to reflect on their SL experience in the middle and at the end of the semester, based on structured reflection prompts. Based on these reflections, the present study aimed to understand the perceived impact of the SL experience on UCP students, particularly on their understanding of sustainable development (e.g., knowledge of SDGs), and the recipients (e.g., knowledge of strategies to achieve SDGs). Qualitative analysis was performed through NVIVO software. The results showed an impact not only on the academic learning and the UCP students’ personal and professional domains, but also on their literacy about the SDGs. According to the UCP students’ perceptions, the SL experience was particularly helpful in promoting SDGs awareness in the recipients and predisposing them to change attitudes and behaviors. Therefore, we conclude that the SL project accomplished its purpose of promoting awareness of the SDGs among the recipients. The implications of these findings are discussed in the context of the role of higher education institutions and SL experiences in sustainable development.